Potosiite and incaite from the Hoei Mine, Japan - Shimizu, Masaaki; Moh, Günter; Kato, Akira (Mineralogy and petrology, 1992)
Potosiite and incaite have been found at the Hoei mine, Oita Prefecture, Japan. Potosiite occurs as tabular crystals (3 cm x 2 cm in size), and is associated with arsenopyrite, pyrrhotite, stannite,jamesonite and pyrite, whereas incaite occurs as polycrystalline aggregates rimming galena or as hair-like masses in a matrix of kutnahorite. X-ray powder data reveal that these minerals are potosiite and incaite, respectively. Electron-microprobe analyses of potosiite and incaite gave the general formula (Pb, Sn)2+6+xFeSb2Sn4+2S14+x, with x < 2. Potosiite is homogeneous, whereas incaite, in contact with galena, is quite heterogeneous. Reflectance data for potosiite show that its bireflectance is one of the lowest among opaque minerals with a sheet-like structure.